Спеціалізовані комп’ютерні засоби для тренування візуальної реакції - Громаков, О. С. (ХНУРЕ, 2020)
The training reaction device was developed to improve Sensory Motor Integration through the visual system. The increased ability to receive visual stimuli, mentally process this information, then react to it with a motor response has vast implications for human performance.
Keywords: тренажер; периферійне сприйняття; швидкість виконання цілісних рухових дій; біоуправління